Pengaruh Intensitas Modal, Intensitas Persediaan, dan Green Investment Terhadap Penghindaran Pajak - darmawan, Sabrina Maharani; Dian Widiyati (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2026)
This study aims to analyze the effect of capital intensity, inventory intensity, and green investment on tax avoidance in consumer non-cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2020 to 2024. This study uses secondary data in the form of annual financial statements obtained from the official website of the Indonesia Stock Exchange. The analytical method used is panel data regression with the assistance of EViews 12 software. The variables in this study consist of capital intensity, inventory intensity, and green investment as independent variables, and tax avoidance as the dependent variable. The results show that partially, inventory intensity has an effect on tax avoidance, while capital intensity and green investment have no effect on tax avoidance. However, simultaneously, the three independent variables have a significant effect on tax avoidance.